he dynamics of change in indicators of coordination abilities of qualified female volleyball players under the influence of using a set of exercises and outdoor games - Alina Melnyk; Ievgeniia Strelnykova; Tamara Liakhova; Natalya Pashchenko (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to study the dynamics of changes in coordination abilities of qualified female volleyball players under the influence of using a set of exercises and outdoor games. Material and methods: the following research methods were used in the research: analysis of scientific and methodological literature; pedagogical experiment; pedagogical testing; methods of mathematical statistics. During the research, the pedagogical experiment was conducted and aimed at increasing the level of coordination abilities of qualified female volleyball players. A group of 10 qualified female volleyball players at the age of 18-21 years of the team "Kharkivyanka" (Kharkiv) was chosen for its holding, who takes part in competitions of teams of the Major League of Ukraine. Such means as a set of special exercises and outdoor were proposed for the development of coordination abilities, and appropriate tests were used to evaluate them. Results: the analysis of the results of the pedagogical experiment showed that the average arithmetic values of the indicators for each of the four selected tests after the experiment were significantly higher compared to the results of the corresponding tests obtained before the experiment. The results of the corresponding comparative analysis using the Student's test proved the validity of the difference between values of the indicators of these tests. Conclusions: the proposed means to increase the level of coordination abilities of female volleyball players justified themselves as effective. They can be used by team coaches in practical work to prepare players for a defensive role, which will contribute to improving the team's game performance in training and competitive activities.